A Hidden Theater Text, Written by Juan Pablo Forner: The Play of Los aduladores - Cañas Murillo, Jesús (2020)
This article rescues from oblivion one of the few plays composed by Juan Pablo Forner in the Spanish Eighteenth Century that we have preserved, but of which there was no news at the present time. It is a comedy, Los aduladores, which was premiered posthumously in Madrid, at the Teatro de la Cruz, in 1797. Various aspects are studied about it: its preservation in libraries, the transmission of its text, its authorship, its sources of composition, the circumstances of its Madrid premiere, the company that took care of its performance, its success among the audience, its echo in the press of the time. It reproduces the only article that was dedicated to him, on the occasion of its premiere, in the newspapers of the time published in Madrid, an article that appeared in print in Memorial Literario, which commented very favourably on his staging, and summarised his argument.